Response of concrete pond–raised Clarias gariepinus fed diets containing different inclusion levels of cow tripe epithelial waste (2004)
The study examined the effect of Cow Tripe Epithelial Waste (CTEW) on the growth performance, nutrient utilization and survival of advanced fry Clarias gariepinus raised in ten homestead tanks (3m x 1.5m x 0.06m) for ten weeks. Each tank was stocked with 100 advanced fry with initial average weight of 0.68±0.55g. The diets were isonitrogenous 40% crude protein and iso-caloric (3.47 ±1.24K cal/g). The fish were fed the equivalent of 5% of their body weight twice daily. The weights of feed were adjusted after bimonthly weighting. The water parameters were monitored at the commencement and weekly subsequenlty. The design of the experiment was completely randomized. The results show that percentage survival, Gross Efficiency Food Conversion (GEFCR) and weight gain were best in the fish fed diet with 25% CTEW replacement. The growth utilization (GEFCR) parameter evaluated was higher in fish fed the diet containing 25% CTEW replacement than those obtained in the control. The Food Conversion Ratio(FCR) of the advanced fry fed the control and diets 1, 2 and 4 were not significantly different (p<0.05). However, the percentage Specific Growth Rate (SGR) improved with increasing CTEW inclusion. It implies that the CTEW protein could qualitatively replace fishmeal in the diets of Clarias gariepinus advanced fry raised in homestead ponds. This is therefore recommended for inclusion in the diets of C. gariepinus for faster growth and better health management.